Call for Papers—Special Issue on the Cultural Construction of Organizational Life - Dacin, Tina; Weber, Klaus (Organization Science, 2007)
Cultural approaches to organization have experienced a renaissance in recent years. The resurgent interest in the cultural construction of organizational life can be seen as a “second wave” of cultural analysis in organization science. The first wave of cultural approaches to organizations paralleled a broader cultural turn in the social sciences in the 1980s, and sparked interest in collective meaning systems at the level of groups, organizations, industries, fields, or countries. An important initial contribution of cultural analysis was to conceptualize contextual constraints on thought and behavior, be it in the form of organizational cultures, national differences, or field-level isomorphism. The current “second wave” of cultural research goes beyond this focus on culture as constraining context, by drawing on recent advances in cultural analysis in sociology, anthropology, psychology, history, and linguistics. Two differences illustrate the resulting expanded agenda for the cultural analysis of organizations: First, culture is construed as both a pragmatic resource and as a contextual constraint. Individuals and firms use cultural materials in strategic ways, but also face questions of power, skill, audience, and variation in the negotiation of meaning. Second, culture is seen as more constitutive than contextual, located inside rather than outside organizing practices. Ideas, moralities, and symbols enable and mediate core processes of organizing, so that questions of how culture is produced, transmitted, and applied become salient. This approach to cultural analysis promises to transcend or at least recast traditional distinctions, such as cultural versus economic explanations, institutional structure versus individual agency, and fabricated versus genuine communication, to name a few. In this special issue, we seek to advance this “second wave” of cultural analysis. We take an expansive view of culture to include a range of symbolic formations and resources, including meaning systems, routines and traditions, frames and logics, codes, language, images, and objects. We welcome theoretical and empirical papers at any level of analysis and using any methodology. We especially encourage submissions that address fundamental questions about the nature and role of culture in organizations and fields, suggest innovative designs and methodologies, or re-examine puzzles in existing research that have not traditionally been examined through a cultural lens. Possible topics include but are not limited to the following questions. (1) Identity and meaning making: For example, processes and resources of identity construction, authenticity, and skillful self-presentation. (2) The production of culture, myth making, and story telling: For example, what role do leaders, organizations, the state, and the media take in shaping collective understandings? What tactics and structures facilitate this task? (3) Tradition and customs: For example, the crafting and experience of organizational heritage and the role of customs and rituals in cultural maintenance and change. (4) The evolution and transformation of central cultural symbols and ideas in organizations: For example, the semiosis of key words, concepts, and artifacts, and evolutionary models of emergence and change in language and codes over time. (5) The cultural construction of markets, competition, and industries: For example, how do language games, social codes, and frames shape competitive and population dynamics?